Profile and determinants of successful aging in the Ibadan study of aging (2014)
OBJECTIVES: To determine the profile and determinants of successful aging in a developing country characterized by low life expectancy and where successful agers may represent a unique group. DESIGN: Community-based cohort study. SETTING: Eight contiguous states in the Yoruba-speaking region of Nigeria. PARTICIPANTS: A multistage clustered sampling of households was used to select a representative sample of individuals (N = 2,149) aged 65 and older at baseline. Nine hundred thirty were successfully followed for an average of 64 months between August 2003 and December 2009. MEASUREMENTS: Lifestyle and behavioral factors were assessed at baseline. Successful aging, defined using each of three models (absence of chronic health conditions, functional independence, and satisfaction with life), was assessed at follow-up. RESULTS: Between 16% and 75% of respondents could be classified as successful agers using one of the three models while 7.5% could be so classified using a combination of all the models. Correlations between the three models were small, ranging from 0.08 to 0.15. Different features predicted their outcomes, suggesting that they represent relatively independent trajectories of aging. Whichever model was used, more men than women tended to be classified as aging successfully. Men who aged successfully, using a combination of all the three models, were more likely never to have smoked (adjusted odds ratio (aOR) = 4.7, 95% confidence interval (CI) = 1.55–14.46) and to report, at baseline, having contacts with friends (aOR = 4.2, 95% CI = 1.0–18.76) or participating in community activities (aOR = 16.0, 95% CI = 1.23–204.40). In women, there was a nonlinear trend for younger age at baseline to predict this outcome. CONCLUSION: Modifiable social and lifestyle factors predicted successful aging in this population, suggesting that health promotion targeting behavior change may lead to tangible benefits for health and well-being in old age.